2015
DOI: 10.1111/wvn.12103
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Brief, Basic Evidence‐Based Practice Course for Clinical Nurses

Abstract: Background: Barriers to the implementation of evidence-based practice (EBP) by nursing professionals include a lack of knowledge, inadequate skills in searching for and appraising evidence, and consulting research articles. However, few studies have addressed the effectiveness of educational interventions to improve their competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(115 citation statements)
references
References 46 publications
(75 reference statements)
7
96
2
8
Order By: Relevance
“…Regarding the origin of each study, only one study was conducted in Europe (Spain)10, and 19 in countries outside Europe including the USA,1123 Taiwan,24 Canada,25 Peru,26 Iran,27 Pakistan,28 and Israel 29. Twelve studies have been published since 2011 10,11,14,15,18,2026.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the origin of each study, only one study was conducted in Europe (Spain)10, and 19 in countries outside Europe including the USA,1123 Taiwan,24 Canada,25 Peru,26 Iran,27 Pakistan,28 and Israel 29. Twelve studies have been published since 2011 10,11,14,15,18,2026.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies have been published since 2011 10,11,14,15,18,2026. Of the 20 studies, 17 were pre–post uncontrolled trials,11,12,1420,2226,28,29 and three were controlled trials 10,21,27. In the studies, the effect of the intervention on the intervention group was compared to the attitudes of the nonintervention control group.…”
Section: Resultsmentioning
confidence: 99%
“…Currently it seems obvious that nurses are aware of the importance of EBP and the use of research, [34,35] but our results show that their knowledge and skills in implementing evidence-based interventions can be improved. Several studies have found a connection between the use of EBP and nurses' knowledge and skills [34,36] and have shown that nurses' knowledge and skills improve after educational interventions. [37][38][39] However, it has been difficult to prove the appropriate form and content of such education.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] However, it has been difficult to prove the appropriate form and content of such education. [36] Mentorship and continuing education are often pointed to as successful strategies. [34,40] In our study, the facilitators trained together in literature searching, analysing scientific articles, the EBP implementation process, and the facilitator role.…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting on the implementation of EBP in health care, Ramos-Morcillo et al (2015) argue that integration of EBP into the clinical practice has "proceeded at a slower pace than desirable" in many health care settings.…”
Section: Implementation Researchmentioning
confidence: 99%